Analysis of tourist satisfaction in realising returns and recommending rural tourism destinations in Jambi province - Haryono, Gampo; Sarmigi, Elex; Siswadhi, Ferry (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The province of Jambi has significant potential in developing rural tourism, with various unique destinations rich in culture and natural beauty that attract visitors. However, the challenge lies in maintaining and increasing tourist visits and encouraging them to recommend these destinations to others. This study aims to analyze the factors influencing tourist satisfaction in realizing repeat visits and recommending rural tourism destinations in Jambi Province. This research employs a survey method by collecting data through questionnaires distributed to 180 tourists who have visited rural tourism destinations in Jambi. The collected data is analyzed using multiple regression analysis techniques with the help of SmartPLS to determine the impact of independent variables on the dependent variable. The results show that the destination image does not significantly influence tourists' intentions to recommend the destination to others but can enhance tourist satisfaction. In contrast, the perceived value by tourists positively impacts the intention to recommend but does not affect satisfaction or repeat visits. The uniqueness of the destination can improve satisfaction and attract repeat visits, although it does not directly influence recommendations. Tourist satisfaction itself does not significantly impact recommendations, and repeat visits do not affect the intention to recommend the destination. The implication of this study is that rural tourism destination managers in Jambi Province need to focus on creating unique experiences and enhancing the perceived value for tourists to improve the appeal and sustainability of the destination.